Effect of convection and cooling on microstructure of mid-chilled solidified casting. (2014) - Chang, W.-S.; Lin, C.-M.; Lei, T.-S.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the effect of convection on mid-chilled solidified castings was investigated. The heat transfer system employed was a cylindrical chilled mould sandwiched between two sand moulds; it was cooled by circulating water. The convection during solidification was investigated on the basis of cooling curve. A comparison of the cooling curves showed that convection reduced the temperature gradient and decreased the solidification time. EPMA analysis results revealed little variation in the stoichiometric ratio, M/C, of carbides. In contrast, M/C of Mo rich carbides varied considerably. The difference of convection in the upward solidified zone resulted in greater segregation, whereas the presence of convection in the downward solidified regions mitigated the problem of segregation. Therefore, shrinkage voids can be prevented and the solidification time can be decreased by placing chilling blocks on top of heavy section castings. In addition, grain coarsening and the degree of segregation can be reduced.